Deformation mechanisms in ionic liquid spun cellulose fibers - Wanasekara, Nandula D.; Michud, Anne; Zhu, Chenchen; Rahatekar, Sameer S.; Sixta, Herbert; Eichhorn, Stephen J. (Elsevier, 2016)
The molecular deformation and crystal orientation of a range of next generation regenerated cellulose fibers, produced from an ionic liquid solvent spinning system, are correlated with macroscopic fiber properties. Fibers are drawn at the spinning stage to increase both molecular and crystal orientation in order to achieve a high tensile strength and Young’s modulus for potential use in engineering applications. Raman spectroscopy was utilized to quantify both molecular strain and orientation of fibers deformed in tension. X-ray diffraction was used to characterize crystal orientation of single fibers. These techniques are shown to provide complimentary information on the microstructure of the fibers. A shift in the position of a characteristic Raman band, initially located at ∼1095 cm−1, emanating from the backbone structure of the cellulose polymer chains was followed under tensile deformation. It is shown that the shift rate of this band with respect to strain increases with the draw ratio of the fibers, indicative of an increase in the axial molecular alignment and subsequent deformation of the cellulose chains. A linear relationship between the Raman band shift rate and the modulus was established, indicating that the fibers possess a series aggregate structure of aligned crystalline and amorphous domains. Wide-angle X-ray diffraction data show that crystal orientation increases with an increase in the draw ratio, and a crystalline chain slip model was used to fit the change in orientation with fiber draw ratio. In addition to this a new model is proposed for a series aggregate structure that takes into better account the molecular deformation of the fibers. Using this model a prediction for the crystal modulus of a cellulose-II structure is made (83 GPa) which is shown to be in good agreement with other experimental approaches for its determination.
Keywords: Cellulose; Fibers; Molecular deformation